LabView design for electronic control interface - Chua, Benny Chong Peng (Nanyang Technological University, 2021)
Measurement Device-Independent Quantum Key Distribution (MDI-QKD) has been widely experimented with and demonstrated. MDI-QKD allows two systems, commonly known as Alice and Bob, to individually transmit Weak Coherent Pulses (WCP) with decoy states in four BB84 polarization states to a mid-way station named "Charlie," which contains a beam splitter. Charlie will measure these WCPs and publicly broadcast Alice and Bob's result to establish an encrypted key. By doing so, an eavesdropper may even impersonate "Charlie" without comprising the distributed key's security, eliminating all detector side-channel attacks. In this project, a control interface for the Silicon Photonic Device is built. The control interface will control the pulse generation, polarization encoding, post-processing, and recording of coincidence events. Experiments will be conducted to evaluate the performance of the control interface connected to the hardware set-up.